The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33225/jbse/20.19.675
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCING FACTORS OF 10th GRADE STUDENTS’ SCIENCE CAREER EXPECTATIONS: A STRUCTURAL EQUATION MODEL

Abstract: Science career expectations can be affected by personal science beliefs and social supports. Framed in Expectancy-Value Models, this research studied the influence of science beliefs (science interest belief, self-efficacy belief and value belief) and social supports (parents and teachers) on students’ science career expectations by the survey of 798 10th grade students. Based on Structural Equation Model, it was found that: 1) science interest belief, self-efficacy belief, value belief and parents’ support ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
(47 reference statements)
1
7
0
2
Order By: Relevance
“…First of all, this study found that ILE, such as visiting STEM related museums, participating in STEM related clubs, competitions and summer camps can promote ISC significantly, which is consistent with previous research results (Kitchen et al, 2018;Maiorca et al, 2021;Nugent et al, 2015). Secondly, students with higher STEM self-efficacy are more confident that they have the ability to engage in STEM careers and achieve good results, and thus more interested in STEM careers (Mohtar et al, 2019;Wang et al, 2020). Thirdly, the clearer the knowledge about STEM career prospects, skills required, and self-development, the more likely students are to make sober and wise decisions.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…First of all, this study found that ILE, such as visiting STEM related museums, participating in STEM related clubs, competitions and summer camps can promote ISC significantly, which is consistent with previous research results (Kitchen et al, 2018;Maiorca et al, 2021;Nugent et al, 2015). Secondly, students with higher STEM self-efficacy are more confident that they have the ability to engage in STEM careers and achieve good results, and thus more interested in STEM careers (Mohtar et al, 2019;Wang et al, 2020). Thirdly, the clearer the knowledge about STEM career prospects, skills required, and self-development, the more likely students are to make sober and wise decisions.…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by theory-based models, such as SCCT (Lent, 1994). Many studies (Halim et al, 2018;Maiorca et al, 2021;Mohtar et al, 2019;Nugent et al, 2015;Wang et al, 2020) have demonstrated that SSE is an important factor for individuals to pursue STEM careers. In this study, SSE was assessed by students' confidence in their own abilities and performance in the four subjects of STEM (Mohtar et al, 2019).…”
Section: Stem Self-efficacy (Sse)mentioning
confidence: 87%
See 1 more Smart Citation
“…Selection of the subject for a better career of a student is a vital task since it is concerned with future employment which influences the whole life of the student and ultimately leads to social development. It is a delegate decision for the students as they are ambitious about it (Batool et al, 2020, Van Dinh et al, 2019, Pratiwi et al, 2020, McKenzie et al, 2020, Wang et al, 2020, Babajide et al, 2020, Orewere et al, 2020. Some students are in confusion or careless to choose a stream.…”
Section: Introductionmentioning
confidence: 99%
“…It has clear purpose, objective reality, strong comprehensiveness, profound inspiration, highlights practice, student-centered, dynamic process, and the results are diversified. Since being introduced to China as a new teaching method in the mid-1980s, case teaching method has gradually been accepted by more and more people, and it has been proved to be an effective and special effect in teaching practice [1]. e participants in the classroom case teaching process include teachers and students.…”
Section: Introductionmentioning
confidence: 99%